2013
DOI: 10.1371/journal.pone.0068704
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Virulence Properties in the C. parapsilosis Sensu Lato Species

Abstract: The C. parapsilosis sensu lato group involves three closely related species, C. parapsilosis sensu stricto, C . orthopsilosis and C . metapsilosis . Although their overall clinical importance is dramatically increasing, there are few studies regarding the virulence properties of the species of the psilosis complex. In this study, we tested 63 C. parapsilosis sensu stricto, 12 C . metapsilosis and 18 C . orthopsilosis isolates for the ability to produce extracellular proteases, secrete lipases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 27 publications
4
77
1
4
Order By: Relevance
“…Indeed, it is widely accepted that aging is associated with a decline in immune function, a process termed immune senescence, which makes an individual more susceptible to infections [36], including opportunistic fungal infections [37]. The assumption that aging is a risk factor for infection with C. metapsilosis could be in line with previous work showing that this yeast is the least virulent species of the group [34,38]. However, to date there are few reports with information about patients' age, and thus, further studies with a greater number of isolates and extensive demographic information are needed to confirm the association between aging and infection by C. metapsilosis.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, it is widely accepted that aging is associated with a decline in immune function, a process termed immune senescence, which makes an individual more susceptible to infections [36], including opportunistic fungal infections [37]. The assumption that aging is a risk factor for infection with C. metapsilosis could be in line with previous work showing that this yeast is the least virulent species of the group [34,38]. However, to date there are few reports with information about patients' age, and thus, further studies with a greater number of isolates and extensive demographic information are needed to confirm the association between aging and infection by C. metapsilosis.…”
Section: Discussionmentioning
confidence: 71%
“…Although intraspecies strain variation can be significant (see, for instance, references 50, 51, 52, and 53), several additional C. parapsilosis species fared no better than did CDC317, the sequenced reference isolate used in most of our studies. Another recent study that looked at a larger set of C. parapsilosis clinical isolates also concluded that, while there were phenotypic differences in vitro, the effects on host interactions were modest (54). The discrepancy between the lab and the clinic might be explained if C. parapsilosis were more common as a commensal or more easily transmitted from person to person, such that patients were exposed to it more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Close relatives include C. orthopsilosis and C. metapsilosis, once characterized as belonging to the same species (Tavanti et al 2005). C. orthopsilosis and C. metapsilosis are much less frequent causes of infection than C. parapsilosis (Table 1) and are less virulent in animal models (Nemeth et al 2013). Comparing the genomes of C. parapsilosis and C. orthopsilosis suggests that amplification of gene families, in particular of cell wall genes, is associated with increased virulence of C. parapsilosis (Riccombeni et al 2012).…”
Section: Post-wgd Speciesmentioning
confidence: 99%